2020
DOI: 10.1093/jxb/eraa082
|View full text |Cite
|
Sign up to set email alerts
|

Reserve lipids and plant autophagy

Abstract: Autophagy is a universal mechanism that facilitates the degradation of unwanted cytoplasmic components in eukaryotic cells. In this review, we highlight recent developments in the investigation of the role of autophagy in lipid homeostasis in plants by comparison with algae, yeast, and animals. We consider the storage compartments that form the sources of lipids in plants, and the roles that autophagy plays in the synthesis of triacylglycerols and in the formation and maintenance of lipid droplets. We also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…Autophagy is a ubiquitous process that plays important roles in plant development and senescence to maintain essential cellular functions and life activities [ 3 , 7 , 19 ]. Extensive studies have indicated that autophagy is important for N utilization [ 26 29 ], fatty acid/lipid homeostasis [ 13 15 ] and the degradation of damaged chloroplasts [ 16 , 17 ] or aggregated proteins [ 18 ] in plants. Although a previous study revealed that autophagy is essential for maintaining the balance of amino acid metabolism in P. patens [ 30 ], how this process regulates C/N status and fatty acid metabolism in moss has been largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is a ubiquitous process that plays important roles in plant development and senescence to maintain essential cellular functions and life activities [ 3 , 7 , 19 ]. Extensive studies have indicated that autophagy is important for N utilization [ 26 29 ], fatty acid/lipid homeostasis [ 13 15 ] and the degradation of damaged chloroplasts [ 16 , 17 ] or aggregated proteins [ 18 ] in plants. Although a previous study revealed that autophagy is essential for maintaining the balance of amino acid metabolism in P. patens [ 30 ], how this process regulates C/N status and fatty acid metabolism in moss has been largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these proteins have homologs in plants. Autophagy plays multiple physiological roles in plants, functioning in processes such as biotic and abiotic stress responses [ 9 , 10 ], anther development [ 11 ], leaf starch degradation [ 12 ], lipid/fatty acid homeostasis and turnover [ 11 , 13 15 ], damaged chloroplast degradation [ 16 , 17 ], soluble/aggregated protein degradation [ 18 ] and senescence [ 2 , 19 ]. ATG3 is an E2-like enzyme involved in the ATG8 and phosphatidylethanolamine (PE) conjugation system during autophagosome formation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The failure to retrieve lipase activity in haustorium and endosperm samples could have come from the fact that a physical association with proteins and, perhaps, peroxisomes is necessary [ 29 ]. Alternatively, lipid remobilization could also involve autophagy, as recently suggested for other seed systems [ 20 ]. In any case, free fatty acids liberated by TAG hydrolysis must then be transferred to the haustorium, where enzymes of β-oxidation are located [ 5 , 7 ].…”
Section: Lipid Remobilizationmentioning
confidence: 99%
“…It is possible that a hormone (such as a gibberellin) is involved but this is presently uncertain (see below the section Control of Germination). In other species with oleaginous seeds, such as Arabidopsis , proteins can also be directed to hydrolysis via the proteasome (summarized in [ 20 ]). Presumably, amino acids produced therefrom can easily penetrate into the haustorium via transporters (currently not characterized in oil palm).…”
Section: Non-lipid Reserve Remobilizationmentioning
confidence: 99%
“…In maize ( Zea mays ), atg12-1 mutant presented a higher LD number, which could reflect active LD assembly or disruption of LD catabolism (Mcloughin et al, 2020). It remains contentious, however, whether autophagy mediates the biogenesis or degradation of LDs in vegetative tissues (Elander et al, 2018; Barros et al, 2020; Masclaux-Daubresse et al, 2020). Although recent studies have clearly revealed an interplay between autophagy and lipid metabolism (Mcloughin et al,2018, 2020; Have et al, 2019; Fan et al, 2019), relatively little is known about the role of autophagy in the mobilization of lipid components under energy limitation conditions.…”
Section: Introductionmentioning
confidence: 99%